The authors describe, very briefly, the main conclusions of the last archaeological work in Castanheiro do Vento, a prehistoric settlement, located in the northeast of Portugal (in the municipality of Vª Nª de Foz Côa). - Jorge, Vítor Oliveira; Muralha, João; Vale, Ana Margarida; Pereira, Leonor Sousa; Velho, Gonçalo Leite (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The authors describe, very briefly, the main conclusions of the last archaeological work in Castanheiro do Vento, a prehistoric settlement, located in the northeast of Portugal (in the municipality of Vª Nª de Foz Côa).